Evaluation of the agreement, adoption, and adherence to the evidence‐based guidelines for the nutritional management of adult patients with head and neck cancer among Australian dietitians. Issue 2 (16th September 2021) - Edwards, Anna; Baldwin, Nathan; Findlay, Merran; Brown, Teresa; Bauer, Judy
Abstract: Aim: Evidence‐based guideline translation to practice can improve outcomes but is often impaired by poor implementation. This project aimed to evaluate the implementation of the Evidence‐based guidelines for the nutritional management of adult patients with head and neck cancer among Australian dietitians providing clinical care to this population. Methods: A questionnaire was developed, with face and content validity confirmed by an expert panel (n = 13), to gauge participant perceptions of the guidelines against an implementation evaluation framework. Dietitians were identified through Dietitians Australia and by contacting experts in the field. Eligibility was determined by questionnaire completion and prior guideline awareness. Responses were provided using a 5‐point Likert scale. Results were analysed using descriptive statistics; with inferential analysis to determine if demographic information could reveal trends in guideline use and perception. Results: Of the 43 initial respondents, n = 28 completed the questionnaire, with n = 24/28 (86%) meeting full eligibility criteria for analysis. Median (range) scores for all four domains were high: awareness (4.0 [3.2‐4.8]), agreement (4.4 [4.1‐4.7]), adoption (3.5 [3.1‐3.9]), and adherence (4.3 [4.1‐4.9]). However, perception of guideline awareness and use among multidisciplinary team colleagues was low (mean 3.2/5.0 and 3.1/5.0, respectively). Dietitians with <10 years' experience had significantly higher perceptions of the guidelines' ability to positively influence practice; support evidence‐based practice; and enhance dietitian credibility ( P = 0.04) vs dietitians with ≥10 years' experience. Conclusion: Dietitians demonstrated high rates of guideline implementation and positive perceptions for its use in clinical practice. Future implementation strategies and evaluation should expand to engage the wider multidisciplinary team and more experienced clinicians.